Electrolyte and battery containing same
By introducing functional additives containing cyano groups and oxygen-containing silane active groups into the electrolyte of lithium-ion batteries, the Si-containing negative electrodes were solved, and the cycling and rate performance of the battery was significantly optimized.
Patent Information
- Application Number
- CN202411864473.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
AI Technical Summary
During the electrochemical process of Si-containing negative electrode, the silicon nanostructure will undergo excessive volume expansion and collapse, resulting in fragility of SEI film, large consumption of electrolyte and lithium ion transmission channels, affecting the stability and performance of the battery.
By introducing specific functional additives into the electrolyte, including cyano groups and oxygen-containing silane active groups, the stability of the negative electrode SEI film is improved, the transition metal dissolution is prevented, and the positive electrode stability is optimized.
The cycle performance and rate performance of the battery are significantly optimized, the stability of the negative and positive interfaces are improved, and the service life of the battery is extended.
Smart Images

Figure CN119725722A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to an electrolyte and a battery containing the electrolyte. Background Art
[0002] Nowadays, people's requirements for the energy density of energy storage devices are increasing. Traditional graphite negative electrodes are increasingly unable to meet the requirements, and Si's theoretical specific capacity of up to 4200mAh / g has attracted much attention. Using silicon-containing materials as the negative electrode of lithium-ion batteries can significantly improve the energy density of the battery, which meets the needs of the current mainstream market. Although the addition of silicon can increase the reversible capacity of the negative electrode and increase the overall capacity density of the battery, the silicon negative electrode also has problems that need to be solved, mainly in the following two aspects: First, the silicon nanostructure of the Si-containing negative electrode will undergo excessive expansion and collapse in volume during the electrochemical process; secondly, the overload change in volume will also cause the SEI film on the Si negative electrode and electrolyte side to continue to break and reorganize, and the properties are abnormally unstable. In the long run, it will greatly consume the electrolyte and greatly affect the transmission channel of lithium ions in the negative electrode, losing the advantages of silicon over traditional carbon-based negative electrodes.
[0003] In view of the problem of silicon negative electrode, developing a new electrolyte that is compatible with it to alleviate the series of problems currently existing in silicon negative electrode is an effective means of improvement. In the carbonate system electrolyte commonly used in existing graphite electrodes, the SEI film formed by the silicon electrode is often fragile and consumes a large amount of electrolyte. The F in LiPF6 - The side reactions with silicon are unconstrained. Therefore, how to develop an electrolyte that is compatible with it is of great significance to further optimize the performance of silicon-containing negative electrode batteries. Summary of the invention
[0004] In order to solve the problems and deficiencies in the prior art, the present application provides an electrolyte and a battery containing the electrolyte. The electrolyte can effectively improve the stability of the SEI film at the silicon negative electrode interface and optimize the stability of the silicon negative electrode by introducing specific functional additives, and can also prevent the dissolution of transition metals and optimize the stability of the positive electrode. As a result, the battery prepared using the electrolyte has significantly improved cycle performance and rate performance.
[0005] According to the first aspect of the present application, an electrolyte is provided, characterized in that it comprises a lithium salt, an organic solvent, and a functional additive; the structural formula of the functional additive is:
[0006]
[0007] In the electrolyte provided in the present application, by introducing the functional additive of the above-mentioned specific structural formula, the functional additive contains cyano and oxygen-containing silane active groups, which can effectively improve the stability of the negative electrode SEI film, especially the stability of the silicon-containing negative electrode SEI film, improve the stability of the negative electrode interface, and also further promote the stability of the positive electrode interface. Therefore, the electrolyte provided in the present application can further optimize the electrochemical performance of the battery, such as cycle performance and rate performance. Specifically, firstly, the oxygen-containing silane active group can react with H2O and HF, and can improve the quality of the negative electrode SEI film by selectively removing HF and H2O, and reduce HF, which can further reduce the corrosion of the high-nickel positive electrode, reduce the dissolution of transition metal ions, improve the stability of the positive electrode, and thus optimize the capacity, cycle performance and rate performance of the battery. Secondly, the cyano group has a strong coordination ability and can combine with the active sites on the electrode surface (such as some high-valent metal ions such as nickel, cobalt, manganese, etc.), thereby masking these active transition metal ions on the positive electrode surface, preventing the dissolution of transition metal ions, reducing the side reactions between the electrode and the electrolyte, and improving the compatibility between the electrode and the electrolyte, thereby improving the electrochemical performance of the battery.
[0008] Moreover, the introduction of the above-mentioned functional additives is also beneficial to improving the overall stability of the electrolyte, reducing the oxidative decomposition of the electrolyte, and at the same time can have a good interaction with other components in the electrolyte without affecting the functions of other components in the electrolyte. It can produce a certain synergistic effect with other components of the electrolyte, so as to further optimize the stability of the negative electrode SEI film and improve the stability of the positive electrode, thereby further optimizing the electrochemical performance of the battery.
[0009] Preferably, R1 includes an alkyl chain or a substituted alkyl chain or any substituent having no less than 5 carbon atoms; R2, R3, and R4 independently include an alkyl chain or a substituted alkyl chain or any substituent having no more than 4 carbon atoms. Ensuring that the carbon number of the alkyl chain or the substituted alkyl chain of each of the above substituents is within the above range can ensure that the functional additive has good solubility and can also enable the functional additive to play a better role, promote the stability of the negative electrode SEI film, and at the same time help to improve the lithium ion transmission efficiency and optimize the overall performance of the battery.
[0010] Preferably, R2, R3, and R4 independently include at least one of methyl and ethyl. When they are methyl and / or ethyl, the oxygen-containing silane active group has higher activity, which is more conducive to the reaction effect of the functional additive with H2O and HF, achieving a better effect of removing H2O and HF, further reducing the interface side reaction, and improving the stability of the negative electrode SEI film, while also further promoting the stability of the positive electrode, thereby further optimizing the cycle performance and rate performance of the battery.
[0011] Preferably, the functional additive includes 11-cyanoundecyltrimethoxysilane, which has the structural formula: Its CAS number is 253788-37-3.
[0012] Preferably, when the functional additive includes 11-cyanoundecyltrimethoxysilane, the mass proportion of the functional additive in the electrolyte is 0.8-3 wt %.
[0013] Preferably, the lithium salt includes a first lithium salt and a second lithium salt; the first lithium salt includes lithium hexafluorophosphate; the second lithium salt includes at least one of lithium trifluoromethanesulfonyl imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl) imide (LiFSI), and lithium dioxalate borate (LiBOB). Further, lithium hexafluorophosphate is selected in the present application for use in combination with other lithium salts. The commonly used lithium hexafluorophosphate can ensure that the electrolyte can maintain good thermal stability and lithium ion transmission performance under high or low temperature environments, and ensure the safety and performance stability of the battery. When it is used in combination with the second lithium salt in the present application, the second lithium salt is equivalent to a lithium salt additive, which can further improve the conductivity of the electrolyte system, promote the stability of the negative electrode SEI film and improve the stability of the positive electrode, thereby helping to maintain the structural integrity and electrochemical performance of the electrode, further improve the energy density of the battery and extend the service life of the battery.
[0014] Preferably, the concentration of the first lithium salt in the electrolyte is 1-1.5 mol / L; the mass proportion of the second lithium salt in the electrolyte is 0.7-4 wt%.
[0015] Preferably, the second lithium salt includes lithium trifluoromethanesulfonyl imide and lithium bis(oxalate borate). Bis(oxalate borate) can form a stable large π conjugated system with a small lattice energy, can combine more ions in the solvent, and can improve the conductivity of the electrolyte system. Lithium trifluoromethanesulfonyl imide can significantly increase the content of LiF, which is one of the main components of the inorganic layer of the SEI film and has the characteristics of stable electrochemical performance and high ionic conductivity. Therefore, it can further promote the improvement of the stability of the negative electrode SEI film, optimize the stability of the negative electrode interface, and thus optimize the electrochemical performance of the battery.
[0016] Preferably, the mass proportion of lithium trifluoromethanesulfonyl imide in the electrolyte is 0.5-3wt%; the mass proportion of lithium bis(oxalatoborate) in the electrolyte is 0.2-1wt%.
[0017] Preferably, the electrolyte further comprises a film-forming additive; the film-forming additive comprises at least one of dithiothreitol sulfate (DTD) and methylene disulfonate (MMDS). The film-forming additive is a low-impedance film-forming additive, which is beneficial to reduce the impedance of the interface film, improve the lithium ion transmission efficiency, optimize the battery electrical performance, etc.
[0018] Preferably, the mass proportion of the film-forming additive in the electrolyte is 0.7-4 wt %.
[0019] Preferably, the film-forming additives include vinyl sulfate and methylene disulfonate. DTD forms a low-impedance film of sulfate at the negative electrode, and MMDS forms some salt-type compounds of methane disulfonic acid at the negative electrode interface, which have low ion transfer impedance. The combination of the two can further reduce the impedance of the interface film, while improving the stability of the interface film, and further optimize the interface stability and the overall performance of the battery.
[0020] Preferably, the mass proportion of vinyl sulfate in the electrolyte is 0.5-3wt%; the mass proportion of methylene cyclomethane disulfonate in the electrolyte is 0.2-1wt%.
[0021] Preferably, the organic solvent includes at least one of linear carbonate and cyclic carbonate.
[0022] Preferably, the volume ratio of the linear carbonate to the cyclic carbonate is 60-80:20-40.
[0023] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate.
[0024] Preferably, the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate.
[0025] Preferably, the organic solvent includes dimethyl carbonate, fluoroethylene carbonate, ethylene carbonate, ethyl methyl carbonate.
[0026] Preferably, the volume ratio of dimethyl carbonate, fluoroethylene carbonate, ethylene carbonate and ethyl methyl carbonate is 10-40:5-15:10-35:25-65.
[0027] According to a second aspect of the present application, a battery is provided, comprising the above electrolyte. The battery prepared using the above electrolyte has improved negative electrode interface stability and positive electrode stability, thereby effectively improving the battery's cycle performance and rate performance.
[0028] Preferably, the battery comprises a negative electrode sheet; the negative electrode sheet comprises at least one of a silicon material and a silicon-carbon material. For silicon or silicon-carbon system batteries, the electrolyte provided in this application has a more obvious optimization of the electrochemical properties of such batteries, such as cycle performance and rate performance.
[0029] Preferably, the battery further comprises a positive electrode sheet, the positive electrode sheet comprises a high-nickel ternary material, and in the high-nickel ternary material, the molar proportion of nickel in nickel, cobalt and manganese is not less than 80%. Furthermore, the electrolyte provided in the present application is more suitable for high-nickel ternary / silicon or silicon-carbon system batteries, and can significantly optimize the electrochemical performance of such batteries. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present application, rather than all of the embodiments.
[0031] Example 1
[0032] 1. Composition and preparation of electrolyte
[0033] The electrolyte in this embodiment includes lithium salt, organic solvent, film-forming additive, and functional additive.
[0034] The lithium salt includes lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonyl imide (LiTFSI), and lithium bis(oxalate borate) (LiBOB). The concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L, the mass proportion of lithium trifluoromethanesulfonyl imide in the electrolyte is 1.7wt%, and the mass proportion of lithium bis(oxalate borate) in the electrolyte is 0.6wt%.
[0035] The functional additive is 11-cyanoundecyltrimethoxysilane, and its mass proportion in the electrolyte is 1.9wt%.
[0036] The film-forming additives include diethylene sulfate (DTD) and methylene disulfonate (MMDS). The mass proportion of diethylene sulfate in the electrolyte is 1.8wt%, and the mass proportion of methylene disulfonate in the electrolyte is 0.6wt%.
[0037] The organic solvent includes diethyl carbonate (DEC), fluoroethylene carbonate (FEC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC), and the volume ratio of diethyl carbonate, fluoroethylene carbonate, ethylene carbonate, and ethyl methyl carbonate is 25:10:20:45.
[0038] The preparation of the electrolyte is carried out according to the following steps: in an argon atmosphere, the lithium salt, functional additives and film-forming additives are mixed evenly in an organic solvent, and stirred at low temperature during the mixing process.
[0039] 2. Preparation of batteries
[0040] Preparation of lithium-ion batteries
[0041] (1) Preparation of positive electrode
[0042] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after vacuum drying and cold pressing processes.
[0043] (2) Preparation of negative electrode sheet
[0044] Silicon-carbon negative electrode material (silicon content is 40-60wt%), conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain a negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on a copper foil through a coating process, and a negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0045] (3) Selection of electrolyte
[0046] The electrolyte prepared in this example is used.
[0047] (4) Selection of isolation membrane
[0048] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0049] (5) Preparation of lithium-ion batteries
[0050] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The bare battery cell is placed in an outer packaging shell, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0051] Example 2
[0052] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the functional additive is adjusted to 3-cyanopropyltrimethoxysilane, the structural formula of which is The rest is consistent with Example 1.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the functional additive is adjusted to The rest is consistent with Example 1.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the functional additive in the electrolyte is adjusted to 0.5wt%; the rest is the same as embodiment 1.
[0057] Example 5
[0058] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the functional additive in the electrolyte is adjusted to 3.5wt%; the rest is consistent with embodiment 1.
[0059] Example 6
[0060] The present embodiment is different from the embodiment 1 in that, in the prepared electrolyte, the lithium bis(oxalatoborate) in the lithium salt is replaced by lithium tetrafluoroborate, and the mass proportion of lithium tetrafluoroborate in the electrolyte is 0.6 wt %; the rest is the same as the embodiment 1.
[0061] Example 7
[0062] This embodiment is different from Embodiment 1 in that, in the prepared electrolyte, lithium trifluoromethanesulfonyl imide is not added to the lithium salt, and the mass proportion of lithium bis(oxalatoborate) in the electrolyte is adjusted to 2.3 wt %; the rest is consistent with Embodiment 1.
[0063] Example 8
[0064] This embodiment is different from Embodiment 1 in that the film-forming additive in the prepared electrolyte contains only vinyl sulfate, i.e., methanedisulfonic acid methylene cyclopentane is not added, and the mass proportion of vinyl sulfate in the electrolyte is adjusted to 2.4 wt %; the rest is consistent with Embodiment 1.
[0065] Example 9
[0066] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the vinyl sulfate in the film-forming additive is adjusted to vinyl sulfite (ES); the rest is the same as embodiment 1.
[0067] Example 10
[0068] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the organic solvent does not contain ethylene carbonate, and the volume ratio of diethyl carbonate, fluoroethylene carbonate, and ethyl methyl carbonate is 25:10:45; the rest is consistent with embodiment 1.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that the prepared electrolyte does not contain any functional additive, that is, does not contain 11-cyanoundecyltrimethoxysilane; the rest is the same as Example 1.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to dodecyltrimethoxysilane, whose structural formula is The rest is the same as implementation 1.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to 11-mercaptoundecyltrimethoxysilane, whose structural formula is The rest is the same as implementation 1.
[0075] Comparative Example 4
[0076] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the functional additive is adjusted to 3-cyanopropyltrimethylsilane, whose structural formula is The rest is the same as implementation 1.
[0077] Test Case
[0078] 1. Experimental Construction Method
[0079] The batteries prepared in all the above examples and comparative examples were tested on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. at room temperature (25°C), and the charge and discharge voltage was limited to 2.5V to 4.2V. The test methods for the first efficiency, cycle and rate performance are as follows:
[0080] 1) First Coulomb efficiency
[0081] At 25°C, the battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, left to stand for 10 minutes, and then discharged to 2.5V at a constant current rate of 0.33C, left to stand for 10 minutes, and the first coulombic efficiency of the battery was calculated.
[0082] First coulombic efficiency (%) = total capacity of the battery at the first discharge at 0.33C / total capacity of the battery at the first charge at 0.33C × 100%.
[0083] 2) Capacity retention rate after 1000 cycles at 1C / 1C at room temperature
[0084] At 25°C, the battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the battery is discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This is considered one charge and discharge cycle. The battery is charged and discharged for 1000 cycles according to the above method, and the capacity retention rate after 1000 cycles of charge and discharge at 1C / 1C is calculated.
[0085] The capacity retention rate (%) of the battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the battery.
[0086] 3) Capacity retention rate at high temperature 45℃ 1C / 1C cycle for 1000 cycles
[0087] At 45°C, the battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the battery was discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate after 1000 cycles of charge and discharge at 1C / 1C was calculated.
[0088] The capacity retention rate (%) of the battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the battery.
[0089] 4) Room temperature 6C rate performance - constant current charging ratio
[0090] At 25°C, the battery was discharged at a constant current rate of 1C to 2.5V and allowed to stand for 10 minutes. Then, the battery was charged at a constant current and constant voltage rate of 6C to 4.2V with a cut-off current of 0.05C. The battery was allowed to stand for 10 minutes. The constant current charging capacity Q1 and the constant current and constant voltage charging total capacity Q2 of the battery were recorded. The 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = constant current charging capacity Q1 / constant current and constant voltage charging total capacity Q2 × 100%.
[0091] 2. Experimental results
[0092] The relevant performance test results of the batteries prepared in all the above embodiments and comparative examples are shown in Table 1.
[0093] Table 1 Related performance test results of batteries prepared in Examples and Comparative Examples
[0094]
[0095] As can be seen from Table 1, the battery prepared using the electrolyte provided by the present application can effectively improve the stability of the SEI film at the silicon negative electrode interface and optimize the stability of the silicon negative electrode by introducing specific functional additives and rationally adjusting the composition of the electrolyte. At the same time, it can also prevent the dissolution of transition metals and optimize the stability of the positive electrode. Therefore, the battery prepared using the electrolyte has good performance in terms of initial efficiency, normal temperature and high temperature cycle performance, and 6C constant current charging ratio. For details, please refer to Examples 1 to 10.
[0096] However, Comparative Example 1 does not contain specific functional additives, and therefore cannot effectively improve the performance of the electrolyte, and therefore cannot effectively improve the stability of the silicon negative electrode SEI film and the positive electrode interface stability, thereby causing a significant decrease in the battery's initial efficiency, room temperature and high temperature cycle performance, and 6C constant current charging ratio.
[0097] The functional additive in Comparative Example 2 does not contain a cyano group, the functional additive in Comparative Example 3 does not contain a cyano group but contains a mercapto group, and the functional additive in Comparative Example 4 does not contain a siloxane group but is directly a silane group, which causes the functional additive to play a role in the electrolyte, reducing its improvement effect on the negative and positive electrode interfaces, and may not be conducive to a good synergistic effect with other electrolyte components, and may even affect the role of other electrolyte components, thereby reducing the overall performance of the electrolyte, and ultimately leading to a decline in many aspects of the battery performance.
[0098] Further comparing Example 1 with Examples 2 and 3, the length of the alkyl chain in the middle of the functional additive or the alkyl chain of the siloxane group in Examples 2 and 3 changes, which will affect the interface improvement effect of the functional additive on the negative electrode and the positive electrode to a certain extent, and is not conducive to the overall performance of the electrolyte, resulting in a decrease in the performance of the batteries in Examples 2 and 3.
[0099] Comparing Example 1 with Examples 4 and 5, the contents of the functional additives in Examples 4 and 5 are too little and too much, respectively, which will cause a decrease in battery-related performance. This shows that the amount of the functional additive added needs to be controlled within a specific range, which is more conducive to the performance of the functional additive and the overall performance of the electrolyte, thereby further optimizing the performance of the electrolyte and the battery.
[0100] Comparing Example 1 with Examples 6 and 7, the second lithium salt in Example 6 is lithium fluoromethanesulfonyl imide and lithium tetrafluoroborate, and the second lithium salt in Example 7 is only lithium dioxalate borate; comparing Example 1 with Examples 8 to 10, the film-forming additive in Example 8 contains only vinyl sulfate, and in Example 9, the vinyl sulfate in Example 1 is adjusted to vinyl sulfite (ES), and the organic solvent in Example 10 does not contain vinyl carbonate. However, the performance of the batteries in Examples 6 to 10 has declined, which shows that the types and combinations of lithium salts, film-forming additives and organic solvents will have a certain impact on the overall performance of the electrolyte, thereby affecting the performance of the battery.
[0101] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. An electrolyte, characterized in that: Including lithium salts, organic solvents, and functional additives; The structural formula of the functional additive is:
2. The electrolyte according to claim 1, characterized in that: R1 includes an alkyl chain or a substituted alkyl chain or any substituent having not less than 5 carbon atoms; R2, R3, and R4 independently include an alkyl chain or a substituted alkyl chain or any substituent having not more than 4 carbon atoms.
3. The electrolyte according to claim 1, characterized in that: R2, R3, and R4 independently include at least one of a methyl group and an ethyl group.
4. The electrolyte according to claim 1, characterized in that: The functional additive includes 11-cyanoundecyltrimethoxysilane, and its structural formula is: The functional additive accounts for 0.8-3 wt % of the electrolyte.
5. The electrolyte according to claim 1, characterized in that: The lithium salt includes a first lithium salt and a second lithium salt; The first lithium salt includes lithium hexafluorophosphate; the second lithium salt includes at least one of lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl imide) salt, and lithium bis(oxalatoborate); The concentration of the first lithium salt in the electrolyte is 1 to 1.5 mol / L; The mass percentage of the second lithium salt in the electrolyte is 0.7-4 wt %.
6. The electrolyte according to claim 5, characterized in that: The second lithium salt includes the lithium trifluoromethanesulfonyl imide and the lithium bis(oxalatoborate); The mass percentage of the lithium trifluoromethanesulfonyl imide in the electrolyte is 0.5-3wt%; The mass percentage of the lithium bis(oxalatoborate) in the electrolyte is 0.2-1 wt %.
7. The electrolyte according to claim 1, characterized in that: It also includes a film-forming additive; the film-forming additive includes at least one of vinyl sulfate and methylene disulfonate; The mass percentage of the film-forming additive in the electrolyte is 0.7-4 wt %.
8. The electrolyte according to claim 7, characterized in that: The film-forming additives include the vinyl sulfate and the methylene cyclomethane disulfonate; The mass percentage of the vinyl sulfate in the electrolyte is 0.5-3wt%; The mass percentage of the methylene cyclomethane disulfonate in the electrolyte is 0.2-1 wt %.
9. The electrolyte according to claim 1, characterized in that: The organic solvent includes at least one of a linear carbonate and a cyclic carbonate; the volume ratio of the linear carbonate to the cyclic carbonate is 60-80:20-40; The linear carbonate comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; The cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.
10. A battery, characterized in that: Comprising the electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolytic solution and lithium ion battery
CN109119685A
Electrolyte for silicon-carbon negative electrode and lithium ion battery
CN110994022A
Electrochemical device and electronic device
CN118352635A
Silicate and organosilicon containing additives for silicon-based li ion batteries
US20230096965A1
Cited By
Modified polymethylhydrosiloxane electrolyte additive, preparation method, electrolyte and application
CN121801096A